Effect of Feed Restriction during Pregnancy on Performance and Productivity of New Zealand White Rabbit Does - Abeer Nafeaa; Souad Abd Elfattah Ahmed; Said Fat Hallah (Veterinary Medicine International)
This study aimed to evaluate effect of stage of feed restriction on performance and productivity of pregnant does. New Zealand white female rabbits were randomly divided into three groups. Control group was provided daily with 185 g of food increased to 200 g from the 15th day of gestation. 𝑅1 was offered daily a restricted amount of food (60% restriction, 111 g) for the first half of pregnancy and then offered 200 g of food daily till parturition. 𝑅2 was provided with 185 g of food daily through the first half of pregnancy and then offered daily a restricted amount of food (60% restriction, 120 g) for the second half. After parturition, food was provided adlibitum. Maternal body weights, litter size, litter weight, and average body weight of kits at kindling of 𝑅1 showed no change, whereas 𝑅2 showed significant reduction in the weights of does at the 4th week of pregnancy and at kindling. The birth weight and weaning weight of 𝑅2 were significantly reduced. The highest mortality was recorded in kits of 𝑅2. No significant differences in blood parameters or serum prolactin were observed. The serum protein was significantly reduced 𝑅2.